ПОЛИФУНКЦИОНАЛНOСТА НА ДА НЕ-ПРАШАЊАТА - Kusevska, Marija; Bužarovska, Eleni; Mitkovska, Liljana (Philological Studies, 2019)
This paper undertakes a pragmatic analysis of da/ne (yes/no)-questions in Macedonian in order to determine their communicative functions in various contexts: offer, encouragement, empathy, disapproval, irony, etc. In comparison to polar dali-questions, which require a positive or negative response, da/ne-questions are biased because they require confirmation of the speaker’s presupposition about the polarity of the answer. This function can be achieved only if the addressee shares common ground and correctly interprets the presupposition of the speaker. The semantic feature of bias makes these questions suitable for signaling positive politeness and small horizontal distance between interlocutors.